HIV Preexposure Prophylaxis Practice among Urban Female Sex Workers in Northwest Ethiopia: Using Generalized Structural Equation Modeling - Lakew Asmare MPH; Atalay Goshu MPH; Tihtna Alemu MSc; Ejigu Gebeye MPH (Journal of the International Association of Providers of AIDS Care)
Background Acquired immunodeficiency syndrome, caused by the human immunodeficiency virus, has remained a public health threat for the last decades with significantly high burden. Despite the introduction of various human immunodeficiency virus (HIV) prevention strategies targeting high-risk populations, including preexposure prophylaxis, there remains a notable gap in the literature regarding Pre-Exposure Prophylaxis (PrEP) practice among female sex workers (FSWs) in Ethiopia, particularly using advanced analytical methods like structural equation modeling. This study aimed to assess practice and associated factors of preexposure prophylaxis among urban female sex workers in Northwest Ethiopia. Methods A cross-sectional study was carried out at organizations of Organizations for Social Service, Health Development, Mehabere Hiwot for Social Development, and African Network for the Prevention and Protection Against Child Abuse and Neglect that serve FSWs. Systematic random sampling technique was employed among 549 FSWs. An interviewer-administered questionnaire was used to collect the data. Generalized structural equation modeling was employed to identify factors associated with PrEP practice. As the mediation of effects was present, the direct, indirect, and total effects were determined. A final model was selected based on the statistical significance of the path coefficient. Results In this study, the practice of preexposure prophylaxis was 28.00% with 95% CI = 25.34% to 32.72%. Thus, female sex workers with an education level of college and above had both direct and indirect positive effects on PrEP practice when mediated by knowledge, knowledge had both direct and indirect effects on PrEP practice when mediated by attitude. Whereas, FSWs who had duration of sex work for 3 to 5 years had only a positive direct effect on PrEP practice compared to those who were living in sex work for less than three years duration. Conclusion However, HIV remains a public health problem, and the practice of preexposure prophylaxis in this study was found to be low. FSWs having higher education levels, attitudes, and knowledge demonstrate a significantly positive effect on their likelihood to practice PrEP. They suggested enhancing their health outcomes and reducing the risk of HIV transmission. The result of this study was also significant for communities that are serving in a given organization targeting integrated HIV testing and counseling services among key populations.